Entretiens de V. Molotov, N. Khrouchtchev, G. Joukov et N. Boulganine avec les journalistes américains W. Hearst, K. Smith et F. Connif - Chroesjtsjov, Nikita; Molotov, Vjatsjeslav; Boelganin, Nikolaj (Paris : Etudes Soviétiques, 1955)
Bibliotheek François Vercammen
Frans
Brochure